Pelatihan Dasar Desain Grafis Menggunakan Aplikasi CorelDRAW Di SMK 1 Ibrahimy Sukorejo - Rudi Ananta Al Hidayah; M. Andrik Muqorrobin Pratama; Zaehol Fatah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Graphic design skills are important in this digital era, butinitial observations show that students still have limitations inmastering design software. Therefore, the CorelDRAW training programaims to equip students with theoretical and practical knowledge inthe use of this application. The training was conducted intensively, coveringintroduction to the interface, basic to advanced features of CorelDRAW, as well ashands-on practice in making various graphic design products such as logos,posters, and pamphlets. Thus, this training not only improvestechnical competence, but also fosters students' interest and potential in the field of graphicdesign. It is hoped that the results of this study can be a reference for otherschools in developing graphic design skills improvement programs that arerelevant to industry needs.